AN ANALIYSIS OF GRAMMATICAL ERROR IN SPEAKING COMMITTED BY THE TOUR GUIDE IN LOVINA SINGARAJA - ., I Kadek Putra Ari Jaya; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., I Nyoman Pasek Hadi Saputra, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini berjenis deskriptif kualitatif yang bertujuan untuk menganalisa kesalahan tatabahasa dalam berbicara yang dilakukan oleh tour guide di Lovina, Singaraja. Dalam penelitian ini, kesalahan tatabahasa difokuskan pada kesalahan tata bahasa yang dilakukan oleh tour guide pada saat berbicara. Data dikumpulkan melalui rekaman suara dari tour guide. Hasil dari penelitian menunjukan terdapat sebanyak 95 kesalahan yang dilakukan oleh tour guide dalam berbicara. kesalahan tersebut antara lain sebanyak 46 (48,42%) verb form error, 15 (15,78%) article error, 5 (5,26%) subject-verb agreement error, 10 (10,52%) word order error, 8 (8,42%) noun error, 7 (7,36%) preposition error, 4 (4,21%) pronoun error, dari hasil tersebut terlihat verb form error merupakan kesalahan yang paling sering dilakukan oleh tour guide saat berbicara. Lebih jauh lagi, hasil penelitian juga menunjukan beberapa faktor penyebab terjadinya kesalahan dalam kemampuan berbicara tour guide berasal dari intralingua transfer, interlingua transfer dan context of learning. Secara khusus kesalahan tata bahasa tersebut dipengaruhi karena the tour guides’ first language, the incorrect translation, the avoidance committed by the tour guide, kurangnya pemahaman dalam bentuk tense dan latar belakang pendidikan secara informal.Kata Kunci : Grammar eror, berbicara, penyebab eror This study was a descriptive qualitative research, which aimed at analyzing the grammatical errors in speaking committed by the tour guides in Lovina, Singaraja. In this study, grammatical errors referred to the errors of using grammar committed by the tour guides in their speaking. This study also concerned with analyzing the factors which caused the grammatical error. The data were collected from the records of the tour guides’ speaking. The results showed that there were 95 errors found in the tour guides’ speaking. Those errors were 46 (48,42%) verb form errors, 15 (15,78%) article errors, 5 (5,26%) subject-verb agreement errors, 10 (10,52%) word order errors, 8 (8.42%) noun errors, 7 (7,36%) preposition errors, 4 (4,21%) pronoun errors in which the most committed error in the tour guides’ speaking was verb form error. Further, it was found the factors which caused grammatical errors came from intralingua transfer, interlingua transfer and context of learning. In specific, the tour guides’ errors were caused by the tour guides’ first language, the incorrect translation, the avoidance committed by the tour guide, misunderstanding of tense form and informal educational background. keyword : grammatical error, speaking, cause of error